Revitalization of KKNI-Based Arabic Language Curriculum in Higher Education - Shofiyani, Amrini (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to conduct a comprehensive evaluation of the implementation of the Arabic Language Education (PBA) curriculum at Universitas KH. A. Wahab Hasbullah (UNWAHA), with reference to the Indonesian National Qualifications Framework (KKNI), and to formulate revitalization strategies that are adaptive to the demands of the industrial world and the developments in contemporary scholarship. The research employs a descriptive qualitative approach within a case study type of evaluative study design. Data were collected through curriculum document analysis and review of the Semester Learning Plans (RPS), in-depth interviews with six lecturers responsible for core courses, and observations of instructional practices in three different classes. The research subjects consisted of sixth-semester students, while the data analysis was conducted using descriptive-analytic methods. The study finds that while the Arabic Language Education curriculum aligns normatively with KKNI level 6 outcomes, several implementation issues remain. These include mismatches between CPL and RPS indicators, limited integration of 21st-century skills, overreliance on teacher-centered methods, low use of digital technologies, and weak stakeholder involvement. To address these, proposed strategies include reformulating graduate profiles based on global and local job market needs, developing RPS using Outcome-Based Education (OBE), improving lecturers’ digital teaching skills, and establishing a collaborative forum with stakeholders such as pesantren, translation agencies, and Islamic media. This reform is urgent to produce graduates who are adaptive, competent, and relevant to current professional demands.